How seasonality and weather affect perinatal health: Comparing the experiences of indigenous and non-indigenous mothers in Kanungu District, Uganda. (August 2017) - MacVicar, Sarah; Berrang-Ford, Lea; Harper, Sherilee; Steele, Vivienne; Lwasa, Shuaib; Bambaiha, Didacus Namanya; Twesigomwe, Sabastien; Asaasira, Grace; Ross, Nancy; ,
Abstract: Maternal and newborn health disparities and the health impacts of climate change present grand challenges for global health equity, and there remain knowledge gaps in our understanding of how these challenges intersect. This study examines the pathways through which mothers are affected by seasonal and meteorological factors in sub-Saharan Africa in general, and Kanungu District (Uganda), in particular. We conducted a community-based study consisting of focus group discussions with mothers and interviews with health care workers in Kanungu District. Using a priori and a posteriori coding, we found a diversity of perspectives on the impacts of seasonal and weather exposures, with reporting of more food available in the rainy season. The rainy season was also identified as the period in which women performed physical labour for longer time periods, while work conditions in the dry season were reported to be more difficult due to heat. The causal pathways through which weather and seasonality may be affecting size at birth as reported by Kanungu mothers were consistent with those most frequently reported in the literature elsewhere, including maternal energy balance (nutritional intake and physical exertion output) and seasonal illness. While both Indigenous and non-Indigenous mothers described similar pathways, however, the severity of these experiences differed. Non-Indigenous mothers frequently relied on livestock assets or opportunities for less taxing physical work than Indigenous women, who had fewer options when facing food shortages or transport costs. Findings point to specific entry points for intervention including increased nutritional support in dry season periods of food scarcity, increased diversification of wage labour opportunities, and increased access to contraception. Interventions should be particularly targeted towards Indigenous mothers as they face greater food insecurity, may have fewer sources of income, and face greater overall deprivation than non-Indigenous mothers. Highlights: This study brings a qualitative lens to a topic primarily studied quantitatively. This approach examines how and why weather and season affect perinatal health. We found the extent weather affected pregnant mothers differs across social groups. The nature of mothers' concerns differed seasonally, which affects interventions.